Educational Policy Concerning the Utilization of Information Technology in Schools: A Short Discussion in the Philippines Context - Romero, Cyril B.; Abano, Ronald C. (The Indonesian Institute of Science and Technology Research, 2025)
This paper explores the educational policies in the Philippines that focus on the integration of information technology (IT) in public schools. It analyzes the core government initiatives, such as the DepEd Computerization Program (DCP), the Public Schools of the Future in Technology (PSOFT) Act, and the establishment of the Public Education Network (PEN). These policies are examined for their objectives, implementations, and impact on educational equity and quality. Furthermore, the study compares these initiatives with similar efforts in other countries, such as Indonesia and Malaysia, to highlight best practices and implementation gaps. The paper also addresses the challenges faced in the implementation of these policies and provides recommendations to optimize the digital transformation of the Philippine educational system.